Diagnosis and Management of Mixed Gestational Trophoblastic Neoplasia: A Study of 16 Cases and a Review of the Literature - Kong, Yujia; Tao, Guangshi; Zong, Liju; Yang, Junjun; Wan, Xirun; Wang, Wenze; Xiang, Yang (Frontiers in Oncology, 2019)
Objective: Mixed gestational trophoblastic neoplasia (GTN) is a rare occurrence that refers to the coexistence of choriocarcinoma and/or placental site trophoblastic tumor and/or epithelioid trophoblastic tumor. The diagnosis and management of mixed GTN are challenging. We investigated the clinicopathological characteristics, diagnoses, treatments, and outcomes of patients with mixed GTN. Materials and Methods: The medical records and pathological sections of 16 patients with mixed GTN who were treated at Peking Union Medical College Hospital and The Second Xiangya Hospital of Central South University between January 2012 and December 2018 were reviewed. Results: Pretreatment serum human chorionic gonadotropin (hCG) levels ranged from 180 to 625,024 IU/L, and were >10,000 IU/L in 14 of the 16 patients, none of whom were diagnosed correctly at initial presentation. Two patients were diagnosed with choriocarcinoma coexisting with intermediate trophoblastic tumor (ITT) through dilation and curettage (D&C) before treatment. Another 5 patients were histologically confirmed to have placental site trophoblastic tumor (PSTT) by D&C but final pathological findings showed mixed PSTT and choriocarcinoma at subsequent hysterectomy. Seven post-chemotherapy patients with an initial clinical diagnosis of choriocarcinoma underwent surgery because of chemoresistance and their pathological findings revealed coexisting ITT. The remaining 2 patients were found to have choriocarcinoma coexisting with ITT following cervical biopsy and pulmonary lobectomy. All patients received chemotherapy: 14 underwent surgery combined with chemotherapy and 2 received chemotherapy alone to preserve fertility. Other than 1 patient who died of disease progression, 15 patients (93.8%) achieved complete remission (CR) after treatment, although 5 (33.3%) relapsed. Of these 5 patients with relapse, 3 achieved CR after additional treatment, 1 was receiving an immune checkpoint inhibitor, and 1 was lost to follow-up after refusing further therapy. Conclusion: Mixed GTN is difficult to diagnose on initial presentation. Overlap of the ITT component should be considered in refractory chemoresistant choriocarcinoma. Coexistence of choriocarcinoma should be suspected in ITT patients with high hCG levels. Surgery combined with chemotherapy is optimal treatment for choriocarcinoma mixed with ITT.